VERBS OF EXCRETION IN TABA - Frederick John Bowden (Masyarakat Linguistik Indonesia, 2014)
This paper describes an unusual pattern of argument marking found in a small number of Taba verbs, all of which have meanings relating to excretion. The verbs concerned are sio ‘to shit’, mio ‘to piss’, sito ‘to fart’, and hantolo ‘to lay eggs’. In normal usage these occur with the excretor argument obligatorily encoded twice, once as a proclitic in the same way that Actor argument are encoded on other verbs, but also as an enclitic, similar to an Undergoer argument with other verbs. While no clear rationale for why these four verbs should be treated differently from all the other verbs in the Taba lexicon, they do all express activities that the performers are only in partial control of, and these verbs may in fact constitute something like a ‘middle voice’ in Taba.